Axial compressive behavior of recycled concrete filled steel tubular stub columns with the inclusion of crushed brick. (August 2020) - Chen, Jie; Zhang, Sumei; Wang, Yuyin; Geng, Yue
Abstract: In China, due to the extensive use of brick as the non-structural walls in the old concrete building, it is hard to exclude the waste brick from the waste concrete in the production of recycled coarse aggregates. This paper investigates the axially loaded recycled aggregate concrete filled steel tubes with the inclusion of crushed bricks as the coarse aggregates, which is called as the recycled brick aggregate concrete filled steel tubes (RBACFSTs). It was found that the compressive resistance only decreased by up to 3.8% when half of the recycled coarse aggregate was substituted by the crushed clay brick (CCB). The structural effects of the CCB replacement are much smaller than the corresponding effects in the material property tests, owing to the confinement effects. The stress states of the steel and the concrete infill were analyzed separately. Model equations to describe the stress–strain responses and the design recommendations for RBACFSTs were proposed.